From Agroforestry to Agroindustry: Smallholder Access to Benefits From Oil Palm in Ghana and the Implications for Sustainability Certification - Khatun, Kaysara; Maguire-Rajpaul, Victoria Alice; Asante, Elizabeth Asiedua; McDermott, Constance L. (Frontiers in Sustainable Food Systems, 2020)
Oil palm production in Ghana – which is primarily cultivated by smallholders (60%+) – plays an important role in local economies and rural livelihoods. As a multi-functional crop, it is embedded in the everyday life of rural and urban Ghanaians both by individual households and on an industrial level. The sector is currently experiencing a resurgence under Ghana’s New Patriotic Party (NPP) rule and is being targeted by the Roundtable on Sustainable Palm Oil (PSPO) for yield intensification and increased export production. End goals of these efforts include poverty alleviation, environmentally responsible development efforts, and agricultural diversification in rural areas. We apply Ribot and Peluso’s ‘theory of access’ (2003) to assess the barriers and opportunities for smallholder oil palm farmers, and the degree to which these are addressed by RSPO interventions. Our results highlight how local producers gain many benefits from palm oil production as a source of regular income, a drought-resilient crop, and a source of cooking oil for household use. However, they also report different levels of access to finance, markets, land, and technical support, along with differing views and visions of the oil palm sector's development. The focus of governmental and RSPO initiatives on international trade-based incentives overlooks this diversity and, in particular, the importance of local markets for Ghanaian livelihoods. This poses a threat to women millers and traders, poorer producers, and the local markets they supply who risk losing access to the palm oil supply chain. More generally, these findings illustrate the importance of understanding how markets interact at multiple local to international scales, in order to design interventions that will more equitably reach and benefit local communities.